IMPLEMENTASI ADKAR APPROACH DALAM PENGELOLAAN LIFESKILLS DI PROVINSI DIY - Entoh Tohani (Jurnal Kependidikan, 2009)
Management of life skills education programs were intended to give benefits for target groups. Attainment of the benefits of the programs depended on how much participation was realized by the target groups. The present study was aimed at providing information as input for developing the quality of the program. The study was qualitative research involving the programs in Yogyakarta Special Province. The results of study showed that of the eight of the programs analyzed, the mayority of the students were aware of the benefits of the programs, move toward involvement, have both intrinsic or extrinsic motivation, have knowedges mainly in the main competencies, and implement the output of trainning on the field of self-efforts or work with others. The implementation of the ADKAR approch was characterized by two traits, namely: human aspects and non-human aspects. So, as conclusion of the study, it was necessary to implement the ADKAR approach continuously for each stage of the management of the life skills education programs.